MARKET DAY AS A PROJECT TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS - A. Arifin; Yusfita Yusuf; Fepi Febianti; Pupung Rahayu Novianti; Nano Nurdiansah (Awang Long Law Review, 2022)
The formation of a Pancasila student profile in students is a form of necessity for a teacher, this is because the Pancasila student profile is a reflection of the success of the education process in Indonesia. The project to strengthen the Pancasila student profile is one of the steps taken in realizing the Pancasila student profile. Entrepreneurship is one of the general themes that can be used as a theme that can be studied by students. The real action in the project with the theme of entrepreneurship is through market day activities. This research was conducted at the international green school Sumedang. The results showed that the market day activities that are usually carried out in schools provide an inculcation of an entrepreneurial attitude to students. This can be seen when students create concepts that will be sold, determine the materials to be processed, process raw materials into ready-to-sell materials, market them, and analyze the advantages and disadvantages they get. In addition, the profile of Pancasila students also develops at every stage carried out in the Market Day project.